2009
DOI: 10.1080/13803390802537636
|View full text |Cite
|
Sign up to set email alerts
|

Short-term longitudinal trends in cognitive performance in older adults with type 2 diabetes

Abstract: Type 2 diabetes is associated with cognitive deficits, although inconsistently across neuropsychological domains. We examined 3-year longitudinal data from the Victoria Longitudinal Study, comparing diabetes (n = 28) and control (n = 272) older adults on a comprehensive neuropsychological battery. Assessing potential change and stability, we found that (a) baseline diabetes group deficits in semantic speed and speed-intensive executive function were preserved, (b) new average deficits for reaction time and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 54 publications
4
39
2
Order By: Relevance
“…Studies of older adults have shown that diabetes is associated with worse cognitive performance but not accelerated cognitive decline(5154). Neuroimaging studies show that diabetes is associated with lower brain volumes but not decreases in brain volumes (55), paralleling the findings for cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of older adults have shown that diabetes is associated with worse cognitive performance but not accelerated cognitive decline(5154). Neuroimaging studies show that diabetes is associated with lower brain volumes but not decreases in brain volumes (55), paralleling the findings for cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a clear effect of education attainment on performance [39]. While semantic memory (listing items/words relating to the category) has been shown to be unaffected, neurocognitive speed (number of words/ items listed in 60s or 90s) appeared deficient in early T2DM-related cognitive decline [40]. Most studies included in this review reported the Verbal Fluency Composite Score rather than the raw scores of its subcomponents, yet task performance was both statistically and clinically significantly poorer in adults with T2DM.…”
Section: Verbal Fluency Taskmentioning
confidence: 97%
“…1,2 Cognitive deficits have been reported across many domains, including executive function, memory, learning, and processing speed. [3][4][5][6][7] Despite this, there is not clear evidence that the rate of decline in cognitive function is accelerated among individuals who have T2DM, with some reporting no difference 4,8,9 and others reporting accelerated rates of decline. 10,11 Using data from an annual battery of cognitive tests administered to a large cohort of women who participated in a trial of postmenopausal hormone therapy (HT), we investigated the longitudinal patterns of relative deficits in domainspecific cognitive assessments among women with T2DM.…”
Section: Introductionmentioning
confidence: 97%